Social Media Marketing Activities and Consumer Brand Engagement: The Moderating Role of Gamification among Generation Z E-Commerce Users - Savitri, Erlina Nadja; Saputro, Julianto Agung (Universitas Proklamasi 45, 2025)
This study examines the effect of Social Media Marketing Activities (SMMAs) on Consumer Brand Engagement (CBE) by considering the moderating role of gamification within the framework of the Elaboration Likelihood Model (ELM). The research focuses on Generation Z as active users of e-commerce platforms in Indonesia. Data were collected through an online survey involving 220 respondents and analyzed using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) approach. The results indicate that the dimensions of entertainment, trendiness, and customization have a significant effect on consumer brand engagement, while interactivity and electronic word of mouth do not exhibit significant effects. Furthermore, gamification is found to strengthen most of the relationships between social media marketing activities and consumer brand engagement, except for the electronic word of mouth dimension. These findings suggest that emotional and experiential factors play a dominant role in shaping Generation Z consumers’ engagement. This study enhances digital marketing literature and provides practical insights for e-commerce companies to develop more effective, experience-focused marketing strategies.